Undiagnosed Bicuspid Aortic Valve: A Silent Danger - HA, Ngow; WMN, Wan Khairina (IIUM Medical Journal Malaysia, 2012)
The normal aortic valve has three leaflets, which are almost equal in size. A bicuspid aortic valve developed as a result of abnormal aortic cusp formation during early embryogenesis. Complications such as valvular stenosis or incompetence are well known. Delayed in identifying the congenital abnormality or the complications may cause morbidity and mortality. We report two cases of congestive cardiac failure as the results of undiagnosed bicuspid aortic valve with severe aortic incompetence. Both young men in their productive age without cardiac risk factors, were unfortunate to present too late. Although one of them was lucky to survive the ordeal, most late presentation ends up gravely. Aortic valve replacement can be offered if early detection is made. Those with severe disease at diagnosis may require a heart transplant.